Febuxostat–p-Toluenesulfonic Acid Multi-Component Crystal: Characterization, Crystal Growth and Elucidation of the Salt/Co-Crystal Nature - Ungur, Doriana T.; Santiso-Quinones, Gustavo; Pop, Mihaela M.; Tamas, Tudor L.; Guguta, Carmen; Stam, Danny; Mija, Alice; Iordache, Coca A. (Crystals (Basel), 2023)
The multi-component solid form of febuxostat (FEB) with p-toluenesulfonic acid was synthesized by solvent-drop grinding and cooling-evaporative crystallization and characterized by powder X-ray diffraction (XRPD), thermogravimetry (TGA), differential scanning calorimetry (DSC), and infrared spectroscopy (FT-IR). The multi-component form was stable after exposure at elevated temperature and relative humidity and powder dissolution measurements revealed five-fold aqueous solubility improvement relative to FEB. Additionally, the decrease in pH after dissolution suggests a potential for enhancing the drug absorption in the lower stomach. In the context of the regulatory requirements, the salt/co-crystal nature of the form was elucidated by a combination of crystallization process development and crystal growth, followed by SC-XRD and FT-IR. Despite the very weak basicity of the drug, crystal structure determination combined with spectroscopy analysis revealed salt formation by the transfer of the acidic proton from p-toluenesulfonic acid to FEB. Our study emphasizes the importance of the crystal structure knowledge in understanding the type of interactions present in multi-component crystals as well as complying with the specific regulatory requirements.